2017
DOI: 10.1371/journal.pone.0186208
|View full text |Cite
|
Sign up to set email alerts
|

Induction of colon and cervical cancer cell death by cinnamic acid derivatives is mediated through the inhibition of Histone Deacetylases (HDAC)

Abstract: Recent studies from our group and many others have shown the ability of histone deacetylase (HDAC) inhibitors for retarding the growth of carcinomas of cervix, colon and rectum in vitro. A search for naturally occurring HDAC inhibitors continues due to the adverse effects associated with known HDAC inhibitors like SAHA and TSA. Therefore in the current study, naturally occurring cinnamic acids derivatives were screened for HDAC inhibitory effect using in silico docking method which identified cinnamic acids as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…We observed increased acetylation of lysine 9 and lysine 14 of histone 3 in the promoter region of CDH1 after the treatment with β-HB, indicating transcriptional stimulation of CDH1 (data not shown). HDACi induced p53-dependent apoptosis in NPC cells (30) and retarded the growth of carcinomas of the cervix, colon, and rectum in vitro (31). Surprisingly, a recent study reported that NPC cells were turned into a mesenchymal cell phenotype after short-term stimulation with the HDACi trichostatin A.…”
Section: Discussionmentioning
confidence: 96%
“…We observed increased acetylation of lysine 9 and lysine 14 of histone 3 in the promoter region of CDH1 after the treatment with β-HB, indicating transcriptional stimulation of CDH1 (data not shown). HDACi induced p53-dependent apoptosis in NPC cells (30) and retarded the growth of carcinomas of the cervix, colon, and rectum in vitro (31). Surprisingly, a recent study reported that NPC cells were turned into a mesenchymal cell phenotype after short-term stimulation with the HDACi trichostatin A.…”
Section: Discussionmentioning
confidence: 96%
“…The widely reported anticancer potential of many natural or synthetic CAD [9,10,13,[33][34][35][36][37][38][39], and the antiproliferative properties of known antimalarial drugs, like chloroquine (2) [69] or quinacrine (4) [70,71], motivated the investigation of CA-antimalarial drug conjugates as anticancer leads. Hence, Pérez et al have investigated the antiproliferative activity of compounds 8 (Figure 2) on MKN-28 (gastric cancer), Caco-2 (colorectal adenocarcinoma), and MFC-7 (breast cancer) cell lines; all compounds were active in the micromolar range, while being non-toxic to the normal HFF-1 (human foreskin fibroblast) cell line.…”
Section: Repurposing Antimalarials For Cancer Via Conjugation To Cinnmentioning
confidence: 99%
“…Depending on their therapeutic targets, different modes of action seem to be exerted by CA and their derivatives or analogues. For instance, interactions with pathogens' membranes have been associated with the antimicrobial action of CA [30][31][32], whereas anticancer properties of different CA have been related to apoptosis [33][34][35][36][37][38][39], which encompasses various events including "S"-cycle arrest [34], cytoskeleton disruption [37], activation of caspases [38], generation of reactive oxygen species (ROS) [35,36], and inhibition of histone deacetylases [33,39].…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al also used 5‐Aza‐dC, which was down‐regulated the DNA methylation of SPARC , to study the progression of T‐cell lymphoma . As a kind of histone deacetylase (HDAC) inhibitors, trichostatin A (TSA) could retard the growth of carcinomas of cervix, colon, rectum and other cancers in vitro . What's more, the co‐treatment of 5‐Aza‐dC and TSA showed a better effect in human gastric cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…22 As a kind of histone deacetylase (HDAC) inhibitors, trichostatin A (TSA) could retard the growth of carcinomas of cervix, colon, rectum and other cancers in vitro. 23 What's more, the co-treatment of 5-Aza-dC and TSA showed a better effect in human gastric cancer cells. 24 In addition, sunitinib, a multitargeted tyrosine kinase inhibitor (TKI), which currently was the standard of care for patients suffering from metastatic renal cell cancer.…”
mentioning
confidence: 99%